The Role of Digital Leadership Capabilities in Enterprise-Wide Digital Transformation - Philipp Goetzinger; Mario Spremić; Božidar Jaković (Foresight and STI Governance, 2025)
In a situation of rapid technological development and the world’s transition to a new technological regime, organizations are faced with the need for digital transformation (DT). This process goes beyond the simple implementation of advanced technologies and involves the management of processes of increased complexity, deep recombinations of business processes, structures, methods of external communications, and so on. However, these factors are not considered by most organizations. In other words, DT is underestimated in terms of complexity, duration, and intensity of adaptation stress. Only 10%-20% of organizations succeed in such a transformation at the first attempt, with large companies failing most often. This study analyzes the reasons why most of these initiatives fail to achieve their goals. Particular emphasis is placed on the link between digital competencies of managers and the impact of technological reforms. For this purpose, an array of relevant publications on the topic of DT over the last five years was analyzed. According to the results, the majority of organizations enter DT without proper preparation in the form of early revision of competencies and corporate culture, going beyond the established models of thinking and behavior, which previously provided competitiveness, but in the new context cease to work. Principles that increase the chances of successful digital transformation are formulated. This article contributes to the growing body of knowledge on management practices in transformational transitions.